2023
DOI: 10.1001/jamanetworkopen.2022.50639
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Novel Macrophage-Regulating Treatment for Wound Healing in Patients With Diabetic Foot Ulcers From the Taiwan Health Care Sector Perspective

Abstract: ImportanceDiabetic foot ulcers (DFUs) and subsequent amputation incur enormous health and economic burdens to patients, health care systems, and societies. As a novel macrophage-regulating drug, ON101 is a breakthrough treatment for DFUs, which demonstrated significant complete wound healing effects in a phase 3 randomized clinical trial, but its economic value remains unknown.ObjectiveTo assess the cost-effectiveness of an ON101 cream added on to general wound care (GWC; ie, conventional treatments for DFUs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(92 reference statements)
1
3
0
Order By: Relevance
“…Wagner grading is currently the most commonly used DFU grading method, which is widely used in clinical practice due to its simplicity, practicality and inclusion of high‐risk feet for DFU. Previous studies have shown a close correlation between DFU amputation and Wagner grading, with a significantly increased risk of amputation for Wagner 4–5 grade foot ulcers compared to 0–3 grade ulcers 18–20 . In this study, as the Wagner grading increased, the amputation rate also showed an upward trend.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Wagner grading is currently the most commonly used DFU grading method, which is widely used in clinical practice due to its simplicity, practicality and inclusion of high‐risk feet for DFU. Previous studies have shown a close correlation between DFU amputation and Wagner grading, with a significantly increased risk of amputation for Wagner 4–5 grade foot ulcers compared to 0–3 grade ulcers 18–20 . In this study, as the Wagner grading increased, the amputation rate also showed an upward trend.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have shown a close correlation between DFU amputation and Wagner grading, with a significantly increased risk of amputation for Wagner 4-5 grade foot ulcers compared to 0-3 grade ulcers. [18][19][20] In this study, as the Wagner grading increased, the amputation rate also showed an upward trend. Through multiple regression analysis, it was found that the Wagner grading was an independent risk factor for DF amputation, which is consistent with previous research results.…”
Section: Discussionmentioning
confidence: 86%
“…Previous clinical trials have focused on diverse strategies to treat DFU, including the delivery of topical recombinant growth factors [ 15 , 45 , 46 , 47 , 48 ], platelet-rich plasma [ 49 ], umbilical cord mesenchymal stromal cells (MSC) [ 50 ], macrophage-regulating drugs (NCT01898923) [ 51 ], or enriched hydrogels with sodium alginate and vitamins. The use of mRNA holds significant promise in the exploration of new pharmaceuticals, especially when upregulation of a protein is desired [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic potential of macrophages in cell‐based therapies has been demonstrated in various clinical trials and preclinical studies. 522 , 559 , 560 Macrophages have outperformed stem cells in specific target diseases, showcasing their outstanding regenerative capacity. 561 Conditions such as kidney disease, stroke, arterial disease, and cancer have been targeted using macrophage‐based therapies.…”
Section: Harnessing Macrophages: Targeting Pathways For Tissue Repair...mentioning
confidence: 99%